IMPLEMENTASI METODE PEMBELAJARAN QISHAH UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SD NEGERI 1 WAKINAMBORO - Wa Darlia; Muhamad Ridwan; Darmayanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the implementation of the qishah learning method and analyze the improvement of students' learning motivation in Islamic Religious Education at SD Negeri 1 Wakinamboro. This study employed a qualitative approach with a case study design. Data were collected through observation, interviews, and documentation. Data analysis used the Miles, Huberman, and Saldana model, encompassing data condensation, data display, and conclusion drawing. The results indicate that the qishah method was implemented through the delivery of Islamic stories relevant to the learning material, the use of communicative language, and the reinforcement of moral values embedded in the narratives. This method proved effective in improving students' learning motivation, as evidenced by increased attention, activeness, and enthusiasm among students in participating in Islamic Religious Education learning. Therefore, the qishah method can serve as an effective alternative for enhancing students' learning motivation in Islamic Religious Education at the elementary school level.